Promotion of improved onion technology through FRG System in Fadis and Babile districts of East Haraghe Zone - Abdulaziz Teha (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
Pre extension demonstration of onion varieties was conducted at Fadis and Babile districts of East Hararghe zone one kebele from one FRG established and 10 trial farmers. Both varieties were sown on 10*10 plot size of demonstration plots with full package technology. The training was given for farmers on onion agronomic practices to make full package technology. The bulb yield of the improved onion varieties (Red Bombay and local) were 22.86, 18.74ton/ha at Erer and 22.00, 17.92 ton/ha Ballina Arba Kebele respectively. The result showed that there was a significant difference between both varieties at <1% level. Red Bombay has a 22.37% yield advantage over local check.